Reframing gambling harms as the product of a predatory industry: A Habermasian interpretation of a Lived Experience-led ‘counterpublic’ - Mills, Thomas; Jenkins, Catherine L.; Grimes, James; Sampson, Jo; Reavey, Paula; Sykes, Susie (Critical Gambling Studies, 2025)
The framing of public health challenges influences how societies and governments respond to them. This paper argues that public health professionals can counter the narrative influence of harmful commodity industries by amplifying the reframing efforts of progressive social movements. We utilise Jürgen Habermas’s ideas to theorise a practical example of a network which shifted narratives to focus on the commercial determinants of gambling harms, offering an original contribution by bridging critical social theory with real-world public health advocacy. Habermasian constructs inform a systematic and theoretically grounded analysis of 33 semi-structured interviews, including people with Lived Experience (LE) of gambling harms. Habermas’s ideas, notably his diagnosis of modern social problems as antagonism between the System and the Lifeworld, provide political-economic context to the emergence of a LE social movement. We show that Habermas’s notion of communicative rationality underpins both the internal dynamics of this movement and public health professionals’ attempt to nurture a ‘counterpublic’ around it: i.e., a space for new ways of thinking and talking about social issues. Paradoxically, the findings reveal the importance and limitations of local collaborations with people affected by harmful industries in the face of those industries’ power, products and advertisements. The findings offer theoretical and practical contributions to commercial determinants research, helping to establish normative foundations and ground it in participatory public health practice.